Anticipatory versus post-shock transfers: Conceptual analysis - de Brauw, Alan; Bloem, Jeffrey R. (CGIAR, 2024)
Climate shocks are becoming increasingly prevalent because of climate change (IPCC, 2023). Moreover, these climate shocks have more potential to negatively affect populations of low- and middle-income countries, as these populations are more likely to be employed in or around agriculture for income generation, which is particularly vulnerable to climate change (Gitz et al., 2016; Clarke et al., 2022). As a result, mechanisms to help these populations build resilience to climate shocks are increasingly needed to mitigate increases in food insecurity as negative shocks occur. One such mechanism, that has become more prevalent in recent years, is anticipatory action. Anticipatory action occurs when governments, donors, humanitarian agencies, or a combination thereof can effectively anticipate a climate shock and act beforehand to provide aid (often in the form of cash transfers) and advice to those who they believe will be affected, rather than waiting until the onset of the climate shock and providing affected households with post-emergency aid. Anticipatory action takes advantage of recent improvements in weather prediction (e.g., Alley, Emanuel, and Zhang, 2019) and can be designed in several different ways to assist potentially affected households and communities maintain assets, shift production patterns, or smooth consumption through a negative climate shock. These methods can include information, which can help households plan for the shock, and cash transfers, to help households implement those plans particularly if they would otherwise be liquidity constrained. Transfers could take place once or, for vulnerable households in longer onset shocks such as drought, they could take place repeatedly over time.